Starbucks’ expressive space: Reading the visual tectonic of architecture driven by colour system - Resza Riskiyanto; Gustav Anandhita (ARSNET, 2022)
This paper argues that colour can be seen as a tectonic instrument to visualise spatial order and generate the surface configuration towards the overall form. Colour plays an important role within a space formation system, more than just a decorative element. Colour demonstrates performance that blurs the surface, presents spatial continuity, or emphasises the presence of space through a well-arranged achromatic-polychromatic colour composition. This paper explores various forms of colour combinations in Starbucks’ interior settings to reveal the performance of colour as part of the functional and expressive space formation system. The study utilises Hue, Saturation, and Lightness (HSL) analysis towards multiple case studies of Starbucks to find out to what extent the formation of a colour system that is specifically made for the identity of a product can be implemented on an architectural scale. The findings introduce another logic of colour systems combination that can be used strategically as a basis for designing architectural spaces.